External shocks and FX intervention policy in emerging economies - Alex Carrasco; David Florián Hoyle (Inter-American Development Bank (IDB), 2021)
This paper discusses the role of sterilized foreign exchange (FX) interventions as a monetary policy instrument for emerging market economies in response to external shocks. We develop a model for a commodity-exporting small open economy in which FX intervention is considered as a balance sheet policy induced by a financial friction in the form of an agency problem between banks and their creditors. The severity of banks agency problem depends directly on a bank-level measure of currency mismatch. Endogenous deviations from the standard UIP condition arise at equilibrium. In this context, FX interventions moderate the response of financial and macroeconomic variables to external shocks by leaning against the wind with respect to real exchange rate pressures. Our quantitative results indicate that, conditional on external shocks, the FX intervention policy successfully reduces credit, investment, and output volatility, along with substantial welfare gains when compared to a free-floating exchange rate regime. Finally, we explore distinct generalizations of the model that eliminate the presence of endogenous UIP deviations. In those cases, FX intervention operations are considerably less effective for the aggregate equilibrium.
Keywords: E32; E44; E52; F31; F41; 330; Foreign exchange intervention; External shocks; Monetary policy; Financial dollarization; Financial frictions